Engineering mathematics IA & IB - Samanta, Guruprasad (Aryan Pub. House, 2023)
Engineering mathematics IA & IB / Samanta, Guruprasad. -- Kolkata: Aryan Pub. House, 2023 510 Sa188v1Av1B No. of Copies : 2